P.006 Neural antibody testing for autoimmune encephalitis: A Canadian single-centre experience. (November 2021) - Mirian, A; McFadden, S; Edmond, P; Bhayana, V; Yang, L; Budhram, A
Abstract : Background: We reviewed our autoimmune encephalitis neural antibody testing using brain tissue indirect immunofluorescence (TIIF) and cell-based assays (CBAs) after one year. Methods: Samples were tested from March 2019–March 2020 by TIIF and CBA for anti-NMDAR, LGI1, CASPR2, AMPAR, GABA(B)R, DPPX, IgLON5 and GAD65. Weakly positive or positive CBA, with or without corresponding TIIF positivity, was reported positive. Clinical questionnaires were submitted for clinical-serological correlation. Patients with a compatible clinical phenotype and no more likely alternative diagnosis were classified as true-positives, while all others were flagged as possible false-positives. Results: Twenty of 373 patients (5.4%) had a positive neural antibody. All anti-LGI1 (N=4), GAD65 (N=4), and GABA(B)R (N=1) were classified as true-positives. In contrast, only 3/6 anti-CASPR2 and 3/5 anti-NMDAR were classified as true-positives. Among true-positives, 2/4 anti-LGI and 3/3 anti-CASPR2 were positive by CBA only. All possible false-positive results exhibited only weak serum staining by CBA, with negative serum TIIF and negative CSF CBA/TIIF (if available). Conclusions: Clinical sensitivity of CBA seems higher than TIIF for neural antibodies studied herein, but may come at some expense to clinical specificity. Among patients with weak serum staining by CBA, correlation with serum TIIF, CSF CBA/TIIF, and clinical presentation is recommended.